2019
DOI: 10.1016/j.cell.2019.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Slow Delivery Immunization Enhances HIV Neutralizing Antibody and Germinal Center Responses via Modulation of Immunodominance

Abstract: Highlights d Slow delivery immunization enhances HIV neutralizing antibody development in monkeys d Slow delivery immunization alters immunodominance of the responding B cells d Weekly longitudinal germinal center (GC) B and T FH analyses provides new GC insights d High-resolution rhesus immunoglobulin locus genomic reference sequence

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
361
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 336 publications
(401 citation statements)
references
References 103 publications
25
361
0
Order By: Relevance
“…Another notable phenotype for the high-titer animals was a different angle of approach by which Fabs bound to the C3/V5-3 epitope: three of six animals exhibited this phenotype, with the low-titer macaques favoring the GH-1 in lieu of this putative high-titer correlate (compare Figure 2 with Figure 3A, 3B, and 3F). This observation was consistent in additional unchallenged low and high-titer animals from the immunization study ( Figure S3D) (Cirelli et al, 2019;Pauthner et al, 2017). Overall, high-titer group displayed an increased diversity in the targeted epitopes, especially with the appearance of V1/V3 binding antibodies, and an associated increase in trimer occupancy ( Figure 3), with apparently unique angles of approach as well, factors that may have contributed to these animals' resistance to infection.…”
Section: High Nab Titer Vaccinated Animals Show the Most Diverse Humosupporting
confidence: 71%
“…Another notable phenotype for the high-titer animals was a different angle of approach by which Fabs bound to the C3/V5-3 epitope: three of six animals exhibited this phenotype, with the low-titer macaques favoring the GH-1 in lieu of this putative high-titer correlate (compare Figure 2 with Figure 3A, 3B, and 3F). This observation was consistent in additional unchallenged low and high-titer animals from the immunization study ( Figure S3D) (Cirelli et al, 2019;Pauthner et al, 2017). Overall, high-titer group displayed an increased diversity in the targeted epitopes, especially with the appearance of V1/V3 binding antibodies, and an associated increase in trimer occupancy ( Figure 3), with apparently unique angles of approach as well, factors that may have contributed to these animals' resistance to infection.…”
Section: High Nab Titer Vaccinated Animals Show the Most Diverse Humosupporting
confidence: 71%
“…The development of GC immune responses is a highly regulated, multifactorial process requiring the spatial organization and (Cirelli et al, 2019). However, we should keep in mind that critical information (i.e., tissue structure, cell-cell positioning) cannot be obtained using FNAs, further emphasizing the importance of using the NHP model.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of antigen in follicles was observed by multiple methods, including by whole organ clarification and by tissue sectioning and immunofluorescent staining. This was the first time that such a process has been shown in NHPs for Env-presenting NPs, although the pattern of antigen deposition is reminiscent of the localization recently shown for animals receiving sustained antigen delivery via osmotic pumps or repeated injections 46,47 . The similarity lends support to the hypothesis that ICs from early antigen-specific IgM and IgG were the driving factors for FDC deposition in those "slow delivery" vaccine administration studies.…”
Section: Discussionmentioning
confidence: 75%
“…However, it has been shown that glycans of soluble Env trimers are recognized by SIGN-R1-expressing macrophages in lymph nodes, leading to capture of Env immunogens in interfollicular regions of lymph nodes following immunization 20,36 . Env immunogen accumulation on FDCs has been demonstrated by using novel immunization strategies that deliver antigen delivery over time periods of several weeks through implanted osmotic pumps or repeated injections 46,47 , but such strategies may not be clinically practical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation